Contemporary Islamic Legal Perspectives on Qualification Policy Politics in Indonesia - Maryanto; Muh. Isna Nurdin Wibisana; Bambang Sumardjoko (MILRev: Metro Islamic Law Review, 2025)
This study investigates contemporary Islamic legal perspectives on qualification policy in Indonesia, with particular attention to the formulation and implementation of standards for public and religious office. It examines how key actors—religious leaders, bureaucratic officials, and academics—perceive, interpret, and respond to these policies within the framework of Sharī‘ah values. Adopting a qualitative, field-based research approach, data were collected through in-depth interviews, participant observation, and document analysis across selected governmental and religious institutions. The findings reveal a persistent tension between the normative principles of Islamic law—such as justice (al-‘adl), public interest (maṣlaḥah), and competence (kifāyah)—and the political realities influencing qualification policies, which are often shaped by administrative logic and pragmatic interests. Although policy discourse frequently invokes the integration of Islamic values, implementation in practice demonstrates that bureaucratic dominance frequently marginalizes substantive Islamic ethical principles. This research contributes to contemporary Islamic legal scholarship by illustrating the interaction between Sharī‘ah principles and legal-political practices in Indonesia. It also provides a normative-critical analytical framework for developing qualification policies that are more just, inclusive, and firmly anchored in Sharī‘ah values while remaining compatible with modern governance structures.